2020
DOI: 10.1155/2020/8844722
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Factors Affecting Flowslide Deposit Morphology Using Taguchi Method

Abstract: Flowslides, as one type of landslides, are becoming a research hotspot due to their high speed and long runout distance, which can cause tremendous damage and economic loss. The scale of damage and deposit morphology of flowslide is closely related to factors like deposit volume, slope height, and slope angle. In order to assess the influence of these factors, a sandbox apparatus is developed, and the Taguchi method is used to design an experimental scheme to analyze the results of factors affecting the deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
2
5
0
Order By: Relevance
“…The reason why the sliding mass spreads radially is because its bottom portion carries water during propagation. The double-upheaval morphology appeared on the surfaces of deposits at high slope angles, which is consistent with previous physical modelling studies (Roche et al, 2011a;Duan et al, 2020;Lajeunesse et al, 2005;Lajeunesse et al, 2006;Lajeunesse et al, 2004) and field investigations (Hutchinson, 2002;Quantin et al, 2004). This morphology was observed by Roche 455 et al (2011a) in a cylinder experiment (where sand was filled into a cylinder that was lifted up rapidly to release the sand), who proposed that it is caused by the wave formed by the impact of later sand to the sand reached already on the horizontal plate.…”
Section: Surface Morphologysupporting
confidence: 91%
See 1 more Smart Citation
“…The reason why the sliding mass spreads radially is because its bottom portion carries water during propagation. The double-upheaval morphology appeared on the surfaces of deposits at high slope angles, which is consistent with previous physical modelling studies (Roche et al, 2011a;Duan et al, 2020;Lajeunesse et al, 2005;Lajeunesse et al, 2006;Lajeunesse et al, 2004) and field investigations (Hutchinson, 2002;Quantin et al, 2004). This morphology was observed by Roche 455 et al (2011a) in a cylinder experiment (where sand was filled into a cylinder that was lifted up rapidly to release the sand), who proposed that it is caused by the wave formed by the impact of later sand to the sand reached already on the horizontal plate.…”
Section: Surface Morphologysupporting
confidence: 91%
“…Of course, the difference in the apparent friction coefficients of these landslides is not only caused by differences in slope angle but also by differences in volume and the type of sliding mass. However, the slope angle has a more significant effect on the apparent friction coefficient (Duan et al, 2020;Huang and Liu, 2009).…”
mentioning
confidence: 99%
“…There are some differences in the names and formulas used to describe this ratio (Scheidegger 1973;Staron 2008;Lucas, Mangeney, and Ampuero 2014;Crosta et al, 2015). It has been referred to as the "Fahrboschung" (Evans and Clague 1994;Geertsema et al, 2006;Hungr 2006), "reach angle" (Scheidegger 1973;Corominas 1996) "effective friction coefficient" (Staron 2008), and "apparent friction coefficient" (Scheidegger 1973;Bouchut et al, 2015;Duan et al, 2020;Yang et al, 2018;Staron 2008;Magnarini et al, 2019;Wang, Sassa, and Fukuoka 2003;Yang et al, 2011;Legros 2002). By associating H/L with the mass of the sliding body, it has been found that a larger sliding mass body results in a lower H/L and stronger landslide movement ability.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments can help to understand the movement mechanism involved in particle flows and have been widely used in research on the movement of geological hazards in recent years. They can also evaluate relevant physical parameters to improve slip distance predictions and verify numerical models (Duan et al, 2020;Iverson, George, and Logan 2016;Ng et al, 2017;H. Q. Yang et al, 2018;Y.-F. Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…When the apparent friction angle is less than the internal friction angle of the soil, it indicates that there may be an effect of reducing frictional resistance during sliding, such as the generation of pore water pressure (liquefaction) [24]. e value of the apparent friction angle of the Miaodian landslide is 10.9° [2,25,26], and the internal friction angle of the saturated loess is about 30° [24]. erefore, it can be suggested that there is a possibility of liquefaction during the sliding process of this landslide.…”
Section: Geological Backgroundmentioning
confidence: 99%